Analysis of Waste Generation in the Gili Trawangan Tourism Area, North Lombok Regency - Wulandari, Titin Juniar; Suripto, Suripto; Ernawati, Ernawati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Gili Trawangan is one of the small island beach tourist destinations on Lombok Island which is famous throughout the world. The beach is used by visitors to enjoy the sunset and sunrise, horse riding, cycling, diving, snorkeling, and canoeing. The problem experienced is that the characteristics of visitors that influence waste generation in the tourist area are not yet known. This study aims to identify visitor characteristics, determine the amount of waste generated and its composition by visitors in the Gili Trawangan beach tourism area. Waste data collection was carried out using direct observation techniques, interviews and document tracing. The results show that waste generation in Gili Trawangan was 0.06 kg/person/day during the high season and 0.05 kg/person/day during the low season. The amount of waste generated by visitors for vocational reasons during the peak season and for healing reasons during the low season was higher than that generated by visitors for other reasons such as filling holidays, tours and business. Visitors with various activities such as snorkeling and playing on the beach produce the highest average amount of waste compared to the amount of waste produced by visitors with other activities such as enjoying the beach, relaxing, walking, working, observing, and taking photos. The components of waste produced by visitors were dominated by kitchen waste both during the high season (52.75%) and the low season (69.91%). Other waste components that are also produced are paper, plastic film, solid plastic, metal and composites.